Cylindrical magnetron based on the plasmaoptical principles - Dobrovol's'kii, A.M.; Evsyukov, A.N.; Goncharov, A.A.; Protsenko, I.M. (Вопросы атомной науки и техники, 2007)
The operation of any magnetron-type sputtering system is based on using of anomalous glow discharge in a crossed E ┴ B fields. In such systems a principle of magnetic isolation of electrons is realized and idea of magnetic lines equipotentialization for control of ions flow on cathode-target can be applied quite well. In the present work, with consistent taking these principles into account, the sample of axially-symmetric cylindrical sputtering system of magnetron type is proposed, elaborated and tested. Використання аномального жевріючого розряду в схрещених електричному та магнітному полях є основою функціонування будь-якої магнетронної розпилюючої системи. В таких системах виконується принцип магнітної ізоляції електронів та може бути застосована ідея еквіпотенціалізації магнітних силових ліній з метою керування iонним потоком на катоді-мішені. На основі послідовного використання вказаних плазмооптичних принципів було запропоновано, реалізовано та досліджено варіант аксіально-симетричної циліндричної розпилюючої системи магнетронного типу. Использование аномального тлеющего разряда в скрещенных электрических и магнитных полях является основой функционирования любой магнетронной распылительной системы. В таких системах выполняется принцип магнитной изоляции электронов и может быть применена идея эквипотенциализации магнитных силовых линий для управления ионным потоком на катоде-мишени. На основе последовательного применения указанных плазмооптических принципов предложен, реализован и исследован вариант аксиально-симметричной цилиндрической распылительной системы магнетронного типа.